Peningkatan Pengetahuan Dan Praktik Ibu Balita Tentang Komposisi Dan Informasi Nilai Gizi Makanan Kemasanan - Marlina, Paramitha Wirdani Ningsih; Rasmada, Sada; Wulandari, Agnes Maharani Puji; Miensugandhi, Aloysius Prima Cahya; Dampang, Damelya Patricksia; Jati, Mateus Bagas Nugroho (STMIK Royal, 2024)
Public awareness and ability to read food labels is still very low. A National Consumer Protection Agency survey stated that 6.7% of people in Indonesia pay attention to the completeness of food labels. One of the Messages of Balanced Nutrition is reading food labels. S1 Nutrition Study Program STIK Sint Carolus together with Nutritionists from the Galur Supporting Community Health Center provided counseling to mothers of toddlers on the topic